NILAI RELIGIUS DALAM NOVEL “BUKAN BUKU NIKAH” KARYA RIA RICIS - Hasian Romadon Tanjung; Mina Syanti Lubis; Nursaini Simbolon (Jurnal Education and Development, 2022)
The purpose of this study was to know the religious values of faith (tauhid), norms of life (fiqh), and behavioral attitudes (morals). The method used in this research is descriptive qualitative and data collection techniques used reading and note techniques. This research was conducted with a period of 3 months. The data of this research are in the form of quotations in the novel and triangulation was used in the validity of the data. The religious values contained in the novel includes 1) faith includes faith in Allah, and piety to Him. 2) behavioral or moral attitudes include patience, humility, trustworthiness, honesty, and sincerity. Religious values are also a benchmark for human behavior. The delivery of religious values in this novel can be found in the interactions of each character in the novel.